Peran Pekerjaan, Peran Keluarga Dan Konflik Pekerjaan Pada Perawat Wanita - Susanti, Sri (Persona:Jurnal Psikologi Indonesia, 2013)
Abstract, This study aimed to find a positive relationship between job role work-family conflict, positive relationship between the role of the family with work-family conflict, job roles and relationships and the role of the family toward Work-Family Conflict in female nurses in the Hospital PT. PETROKIMIA GRESIK. Sampling in this study conducted with a purposive sampling method with consideration of (judgment) specific, namely: nursing women who are married and have children. The number of samples in this study were 70 respondents. Data was collected by survey methods and distributed questionnaires to the respondents. Testing the hypothesis in this study using multiple regression analysis. The results of hypothesis testing showed that there was no positive relationship between the role of work-family work, it can be seen from the value of sig. 0.321 (> 0.05). For the second hypothesis in this study proved to be acceptable, with sig. 0.01 (<0.05) means that the role of the family has a positive relationship with work-family conflicts for the job role and the role of the family also proved capable of simultaneously dealing with work-family conflict, amounting to 0.201, suggesting that the role of job and the role of the family were able to collectively affect or contribute to work-family conflict by 20%, while other factors of (100% - 20% = 80%) is influenced by other variables that are not observed in the study.Keywords: Role of Work, Family Roles and Work-Family Conflict